Vivienda de interés social con implementación de un sistema pasivo para lograr su eficiencia energética - Orrala Ramírez, Marjorie Lissette (2024)
Thermal comfort inside a dwelling is very important for humans, since it is there where they spend a large part of the day and of their lives, but due to the high radiation that exists in the city of Guayaquil, people choose to use appliances to create a cool environment inside their homes, but this leads to high costs in electric bills, however in December of last year the country had an energy deficit which considerably harmed the population, especially businesses and homes, it is for this reason that in this project prototypes of social interest housing have been designed with the implementation of a passive system to achieve their energy efficiency, they also have an energy self-efficiency system through a photovoltaic system using solar panels. This project is located in the Monte Sinai sector, since it is a sector that has been developing without any ordinance over the last few years, and does not have the necessary equipment and services for its comfort. As this degree work has developed, it has become necessary to create three housing prototypes for the different families that live in the sector and thus achieve the desired objectives by creating a sustainable and resistant home against any climate change...........